2012
DOI: 10.4049/jimmunol.1103065
|View full text |Cite
|
Sign up to set email alerts
|

Actin Reorganization Is Required for the Formation of Polarized B Cell Receptor Signalosomes in Response to Both Soluble and Membrane-Associated Antigens

Abstract: B-cells encounter both soluble (sAg) and membrane-associated antigens (mAg) in the secondary lymphoid tissue, yet how the physical form of Ag modulates B-cell activation remains unclear. This study compares actin reorganization and its role in BCR signalosome formation in mAg- and sAg-stimulated B-cells. Both mAg and sAg induce F-actin accumulation and actin polymerization at BCR microclusters and at the outer rim of BCR central clusters, but the kinetics and magnitude of F-actin accumulation in mAg-stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
134
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(140 citation statements)
references
References 55 publications
6
134
0
Order By: Relevance
“…Moreover, both our studies and those of others showed that these accumulation events are sensitive to the biochemical and biophysical features of the antigens that B cells likely encounter in vivo (4,5). These features include but are not limited to antigen density (6,7), antigen affinity (6,7), antigen valency (8)(9)(10)(11)(12)(13), the mobility of the antigen (14)(15)(16)(17), the stiffness of the substrates presenting the antigen (18,19) and the mechanical forces delivered to the BCRs by the antigens (20,21). These facts highlight a long-standing question in immunology: how can the initiation of B-cell activation process the information of antigen specificity, density, affinity, valency, mobility, substrate stiffness, and mechanical forces in such an efficient way?…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, both our studies and those of others showed that these accumulation events are sensitive to the biochemical and biophysical features of the antigens that B cells likely encounter in vivo (4,5). These features include but are not limited to antigen density (6,7), antigen affinity (6,7), antigen valency (8)(9)(10)(11)(12)(13), the mobility of the antigen (14)(15)(16)(17), the stiffness of the substrates presenting the antigen (18,19) and the mechanical forces delivered to the BCRs by the antigens (20,21). These facts highlight a long-standing question in immunology: how can the initiation of B-cell activation process the information of antigen specificity, density, affinity, valency, mobility, substrate stiffness, and mechanical forces in such an efficient way?…”
supporting
confidence: 62%
“…Interestingly, the termination of the probing behavior seems to be dependent on the interactions between the BCR and antigen molecules, as neither the interaction between MHC-I and anti-MHC-I antibodies, nor that between integrin and the adhesion molecule ICAM-1, terminated the B-cell probing behaviors. This highly selective and strict dependence on the interactions between the BCR and antigen molecules may be linked to the welldocumented actin remodeling events in response to BCR and antigen recognition (15,16,28,29). All these in vitro data support the early intravital imaging studies, which showed that B cells terminated the migratory behavior on recognition of cognate antigens on the surface of antigen-presenting cells (APCs) and subsequently developed an enlarged contact interface for the acquisition of the antigenic information (37,38).…”
Section: Discussionmentioning
confidence: 59%
“…As such, microclusters seem to function both as hotspots for signaling and units for antigen transportation to facilitate their subsequent endocytosis. The actual mechanism of microcluster movement to the synapse center is not well defined but has been suggested to involve passive movements along centripetal, rearward actin flow (59). TCR microcluster mobility has been associated, in motile T cells, with actin depolymerization that increases toward the filamentous actin (F-actin) poor cSMAC (60).…”
Section: Pla (Proximity Ligation Assay)mentioning
confidence: 99%
“…The cSMAC exhibits very low levels of F-actin, however, the formation of the central antigen cluster is dependent on active actin dynamics (10). Indeed, actin polymerization is sustained in the pSMAC and can continue gathering new antigen from the APC surface (59). Further pointing toward synapse plasticity and ability to collect more antigen over time, it has also been reported that B cells are able to move along the surface of APC while maintaining the IS structure (19).…”
Section: Synapse Maturationmentioning
confidence: 99%
“…Actin reassembly expands the contact of B cells with Ag-presenting surfaces and induces polarized movement of surface BCRs, enhancing BCR clustering and signaling (8-10, 12, 13). Upon maximal cell spread, F-actin decreases in the B-cell region contacting Ag-presenting surfaces, and the cells contract, facilitating coalescence of BCR microclusters and signal attenuation (1,8,9,13). Persistent actin accumulation at the B-cell contact zone and delayed cell contraction, caused by B-cell-specific neuronal Wiskott-Aldrich syndrome protein (N-WASP) knockout, lead to enhanced BCR signaling and elevated levels of autoantibody (autoAb) (14).…”
mentioning
confidence: 99%